Features of the professional training of engineers at German universities in the dual education system (Pedagogy of Higher and Secondary Education, 2013)
Garasyuta V. M. Features of the professional training of engineers at German universities in the dual education system.The article deals with the key questions of the organization of training engineers at German universities in the dual education system. The advantages of training future professionals in the process of dual training are considered. The requirements for future engineers from businesses and educational institutions are provided. The employability possibilities of graduates are set out.
Keywords: vocational training; dual education; training; engineer